Death in a Prairie House : Frank Lloyd Wright and the Taliesin Murders. (University of Wisconsin Press, 2007)
The most pivotal and yet least understood event of Frank Lloyd Wright's celebrated life involves the brutal murders in 1914 of seven adults and children dear to the architect and the destruction by fire of Taliesin, his landmark residence, near Spring Gre.